K-means clustering algorithm in image recognition tasks (Transport systems and technologies, 2019)
The article is an overview of the scientific direction of graphic image recognition based on the k-means clustering algorithm. In particular, we have analyzed the clustering of data in digital image identification problems; we have described the operation principle of this algorithm with an illustration, where the number of selected clusters is equal to two and we presented a block diagram of the algorithm. We have proposed a scheme for implementing a machine vision system using this algorithm in the process of detecting overheated sockets on rail. We have performed color-based segmentation simulations over infrared images to detect high temperature sections in MATLAB. More specifically: two conditional images are taken, showing the railroad socket, one of which is normal and the other is overheated. The simulation results show that color-based segmentation allows accurate segmentation of thermal imaging. The application of this algorithm in the process of creating software for thermographic cameras for the purpose of recognizing temperature is effective, because this algorithm enables image compression, speeds up data processing, and enables the thermal performance of railroad socket to be monitored at high speeds.
Keywords: image, algorithm, clustering, simulation, segmentation, temperature, railroad socket.